Retaliation, Obedience Pressure, and Investigative Decisions on Whistleblowing Allegations: An Experimental Study - Frida Fanani Rohma; Rahayu Dewi Zakiyah (Jurnal Dinamika Akuntansi, 2022)
Purposes: We investigate the interplay between retaliation and obedience pressure and the effect of the interplay on investigative decisions on whistleblowing allegations. The obedience pressure theory was employed to elaborate on the effect of obedience pressure and retaliation on individual behaviors.Methods: This research used experimental laboratory method with a between-subjects 2x2 factorial design. Retaliation is manipulated into two, i.e., strong vs. weak, and obedience pressure is also manipulated into two, i.e., high vs. low. Accounting students were the research participants and served as substitutes for practitioners to avoid any social desirability bias.Findings: This research found the moderating effecf of obedience pressure on retaliation and investigative decisions on whistleblowing allegations relationship. Individuals’ inclination to be a steward may be the factor elucidating their behaviors under the retaliation and obedience pressure conditions. Egoist reasoning boosts individual predisposition to avoid potential risks s/he may have to face.Novelty: This study fills a gap in the literature on whistleblowing which has been discussed a lot from the whistleblowing perspective. This study expand the study by highlighting the retaliation and obedience pressure as environmental factor that determine the whistleblowing effectiveness from recipient perspectives.